2017
DOI: 10.1111/bjh.14914
|View full text |Cite
|
Sign up to set email alerts
|

A clinical risk score for pulmonary artery thrombosis during acute chest syndrome in adult patients with sickle cell disease

Abstract: Pulmonary artery thrombosis (PAT) is involved in lung vascular dysfunction during acute chest syndrome (ACS) complicating sickle cell disease (SCD). No clinical score is available to identify patients eligible for multi-detector computed tomography (MDCT) angiography during ACS. This retrospective study aimed to develop a risk score for PAT during ACS (PAT-ACS risk score). Patients with SCD were investigated by MDCT during ACS. A logistic regression was performed to determine independent risks factors for PAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…6,13,37 Lung CT data were available for 57% of the episodes of ACS but only 2 of the 60 (3%) evidenced PE. This prevalence of PE is lower than 12%-17% observed in two recent French studies of ICU patients with severe ACS, 38,39 although the discrepancy might be due to differences in severity. This prevalence is also lower than the value of 9.8% reported by Vichinsky et al, although the researchers did not have CT data for all episodes.…”
Section: Discussioncontrasting
confidence: 71%
“…6,13,37 Lung CT data were available for 57% of the episodes of ACS but only 2 of the 60 (3%) evidenced PE. This prevalence of PE is lower than 12%-17% observed in two recent French studies of ICU patients with severe ACS, 38,39 although the discrepancy might be due to differences in severity. This prevalence is also lower than the value of 9.8% reported by Vichinsky et al, although the researchers did not have CT data for all episodes.…”
Section: Discussioncontrasting
confidence: 71%
“…However, the triggering events of ACS in SCD patients may vary. Although conventional wisdom suggests ACS occurs secondary to fat embolism in SCD, more recent evidence from CT studies has demonstrated in situ pulmonary thrombosis in 10-20% of ACS patients [33][34][35][36][37][38][39][40]. Interestingly, in 16% of 538 SCD patients with ACS, pulmonary infarction or thrombosis were the triggering events rather than infection or fat embolism [41].…”
Section: Pathophysiology Of Sickle Cell Disease and Covid-19mentioning
confidence: 99%
“…Over the last 2 years, 1860 patients were hospitalized for VOC at Henri Mondor hospital, of whom 720 (38.7%) had a chest X‐ray. We therefore propose a new algorithm for the diagnosis of ACS (Figure 1 ), primarily based on lung auscultation, the risk for pulmonary artery thrombosis, 8 and clinical severity as defined by the French guidelines. 6 The algorithm promotes the use of imaging only when clinically relevant, and favors the use of ultrasound over X‐ray, except for patients at risk for pulmonary artery thrombosis or with clinical severity, that require CTPA.…”
mentioning
confidence: 99%